LOCOMOTOR INJURIES IN COMBAT SPORTS: SYSTEMATIC REVIEW - Živković, Mladen; Mekić, Amel; Furunović, Slobodan; Stojanović, Nikola; Milošević, Nikola; Đošić, Anđela; Živković, Danijela (Physical Education and Sport Through The Centuries, 2024)
The aim of this research was to analyze locomotor injuries in combat sports based on a systematic review of previous studies. The sample consisted of martial arts athletes (judo, karate, wrestling, kickboxing and taekwondo) of both sexes, aged 11-49 years. Survey questionnaires and medical reports were used as measuring instruments for assessing injuries in the research. The found data, presented numerically and in percentages, were used for further analysis. The results of this research show that the characteristics of injuries of the locomotor system in martial arts usually do not depend on the sex of the respondents. There is a higher frequency of injuries in competitions and lower in training (except for under-18s). The most common locations of injuries (head and neck, extremities and joints), types of injuries (contusions, bruises and fractures), and severity of injuries (mild, moderate, or severe) depended on the characteristics of martial arts (sports techniques, tactics, physical and mental fitness, etc.). By applying additional methods, by improving physical preparation that is adequately dosed with the improvement of technical and tactical elements, injuries to athletes could be prevented.